Evolution and co-evolution of regional innovation processes. Issue 9 (2nd September 2019) - Fritsch, Michael; Kudic, Muhamed; Pyka, Andreas
ABSTRACT: Focusing on 'evolution and co-evolution of regional innovation processes', this special issue addresses a highly topical subject. The contributions cover a number of distinct but complementary issues of innovation processes at the regional level and provide rich insights for the improvement of regional policy designs. This editorial outlines the general theme of the special issue and briefly summarizes the main results of the contributions. It ends with some critical considerations and an outlook on future research needs.